2019
DOI: 10.14336/ad.2018.0817
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Hypothyroidism: is it Really Subclinical with Aging?

Abstract: No recent study has focused on clinical features of subclinical hypothyroidism (SCH), especially in older patients. TSH measurement has remarkably evolved these last 20 years and thus reconsideration is needed. In our prospective multicenter study (2012-2014) including 807 subjects aged <60 years (<60y) and 531 subjects ≥60 years (≥60y), we have monitored 11 hypothyroidism-related clinical signs (hCS) together with TSH, FT4, FT3 and anti-thyroperoxidase antibodies values. hCS expression has been compared in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
3
0
1
Order By: Relevance
“…In a randomized controlled trial for thyroid hormone replacement for untreated older adults with SCH, it was shown that the levothyroxine therapy in the elderly patients diagnosed with SCH provided no symptomatic benefit [ 42 ]. Moreover, it has been shown that elderly patients diagnosed with SCH under current guidelines do not strongly express the clinical signs of hypothyroidism compared to younger SCH patients, and this may further support the inadequacy of using the same guidelines for diagnosing SCH in the elderly population [ 8 ]. Ultimately, we must be cautious when diagnosing and treating SCH in older patients, and a guideline for age-based reference range of TSH is needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a randomized controlled trial for thyroid hormone replacement for untreated older adults with SCH, it was shown that the levothyroxine therapy in the elderly patients diagnosed with SCH provided no symptomatic benefit [ 42 ]. Moreover, it has been shown that elderly patients diagnosed with SCH under current guidelines do not strongly express the clinical signs of hypothyroidism compared to younger SCH patients, and this may further support the inadequacy of using the same guidelines for diagnosing SCH in the elderly population [ 8 ]. Ultimately, we must be cautious when diagnosing and treating SCH in older patients, and a guideline for age-based reference range of TSH is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Subclinical hypothyroidism (SCH) represents an early form of thyroid dysfunction and is biochemically defined as an elevated TSH (thyroid-stimulating hormone or thyrotropin) level with a normal level of free thyroxine (FT4) within the reference range [ 1 ]. SCH can affect about 1–11% of adults depending on the cohort studied, and such wide variability in its incidence can be attributed to the environmental and ethnic differences as well as the different TSH reference ranges used in each country [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…A number of different researchers have suggested a criterion for treatment but only when there are signs and if the TSH level is >10 mIU/L or >20 mIU/L [14]. In subjects of 60 years and older, some of the signs for Shypo are not as clearly diagnosed as in those under 60 years [32]. TSH values may increase with age, which should lead to a more cautious interpretation of TSH in subjects aged over 60.…”
Section: Discussionmentioning
confidence: 99%
“…Peningkatan kadar TSH pada hipotiroid subklinis menunjukkan telah terjadi hipofungsi tiroid ringan. Hal ini disebabkan karena hubungan antara TSH dengan FT4 disirkulasi bersifat loglinear didasarkan pada mekanisme umpan balik negatif hipotalamus-hipofisis-tiroid (H-P-T) (Hidayat & Susbiantonny, 2018), sehingga FT4 yang berkurang dalam jumlah kecil akan berkorelasi dengan peningkatan logaritmik TSH (Gourmelon et al, 2019). Konsentrasi iodium yang tinggi menyebabkan terjadinya penurunan ringan kadar hormon tiroid dan peningkatan kadar TSH ke batas atas kisaran normal telah dilaporkan pada beberapa penelitian.…”
Section: Hasil Dan Pembahasanunclassified